Analisis Tematik Penulisan Tentang Hak Kebebasan Beragama Di Portal Berita Malaysiakini - Kamal Azmi Abd Rahman; Ain Balkis Mohd Azam; Sarjit Singh; Abd Ha-kim Mohad; Khadijah Muda; Adibah Sulaiman (USIM Press, 2024)
AL-I’LAM –J. Contemp. Islam. Comm. & Media Volume 3 No.2 Page (1-19)